2021
DOI: 10.1093/g3journal/jkab050
|View full text |Cite
|
Sign up to set email alerts
|

Rapid divergence of the male reproductive proteins in theDrosophila dunnigroup and implications for postmating incompatibilities between species

Abstract: Proteins involved in post-copulatory interactions between males and females are among the fastest evolving genes in many species, usually attributed to their involvement in reproductive conflict. As a result, these proteins are thought to often be in the formation of postmating-prezygotic incompatibilities between species. The Drosophila dunni subgroup consists of a dozen recently diverged species found across the Caribbean islands with varying levels of hybrid incompatibility. We performed experimental crosse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…In our study, the eggs laid by N-line females mated with H-line males hatched at a 25% lower proportion compared to the intra-line crosses, suggesting a reduction in egg fertilization, and thus zygote formation. While post-mating pre-zygotic isolation is still a developing area of research, many studies have demonstrated the involvement of seminal fluid proteins in egg fertilization failure and defective sperm storage (Marshall et al 2009;Larson et al 2012;Ahmed-Braimah 2016;Garlovsky et al 2020;Hill et al 2021). A plausible explanation for our results may be differences in seminal fluid proteins between males of both lines which could affect egg fertilization rates and/or female sperm utilization.…”
Section: Egg Hatchabilitymentioning
confidence: 60%
See 2 more Smart Citations
“…In our study, the eggs laid by N-line females mated with H-line males hatched at a 25% lower proportion compared to the intra-line crosses, suggesting a reduction in egg fertilization, and thus zygote formation. While post-mating pre-zygotic isolation is still a developing area of research, many studies have demonstrated the involvement of seminal fluid proteins in egg fertilization failure and defective sperm storage (Marshall et al 2009;Larson et al 2012;Ahmed-Braimah 2016;Garlovsky et al 2020;Hill et al 2021). A plausible explanation for our results may be differences in seminal fluid proteins between males of both lines which could affect egg fertilization rates and/or female sperm utilization.…”
Section: Egg Hatchabilitymentioning
confidence: 60%
“…Post-mating pre-zygotic isolation in the form of reduced egg hatchability is commonly observed among insect taxa (Price et al 2001;Matsubayashi and Katakura 2009;Marshall et al 2009;Garlovsky and Snook 2018;Hill et al 2021).…”
Section: Egg Hatchabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Flexibility in SC composition may explain how these molecular transitions are possible without major fitness impacts, but cannot account for why SC genes appear to be evolving under recurrent adaptation. The recent explosion of high quality Drosophila species genome assemblies (31)(32)(33)(34)(35)(36)(37) offer a unique opportunity to understand the genetic and evolutionary mechanisms driving the strikingly rapid divergence of SC genes. Here, we systematically revisit the evolution of the SC in Drosophila by examining the genomes and transcriptomes of 48 species scattered across the entire Drosophila phylogeny, with dense representation from three key species groups (melanogaster, obscura, and immigrans).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, spermatozoa exhibit an extraordinary diversity in morphology across taxa 13 , 14 . Also, the genes coding the gamete surface proteins or seminal fluid proteins belong to the fastest evolving genes in the genome 8 , 15 , 16 . Despite the growing number of examples showing the importance of PMPZ isolation in speciation 6 , 15 17 , we still know very little about molecular and physiological mechanisms underlying PMPZ isolation 4 .…”
Section: Introductionmentioning
confidence: 99%